The relationship between fun at work and work engagement / Mohd Fazil Jamaludin, Nordiyana Mohammed Shobri, Azlyantiny Mohammad - Jamaludin, Mohd Fazil; Mohammed Shobri, Nordiyana; Mohammad, Azlyantiny (Institute of Research Management & Innovation (IRMI), 2013)
This study was designed to address two questions. First, what are the scores for fun at work that affect work engagement? Second, what is the relationship between fun at work and work engagement? In order to address these questions, analyses were conducted from a sample of 66 respondents. The result of these analyses found that socializing with co-workers was the highest mean score compared than other fun at work scale. Overall, there are various results from the relationship between fun at work scale (socializing with co-workers, celebrating at work, personal freedoms, and global fun at work) and work engagement. Specifically, there was a positive significant relationship between fun at work and work engagement. Thus, as fun at work increase, the work engagement will also increase.